Evolution, Challenges, Mobile Application Tools and Framework: A Literature Review - Meilvin Wijaya; Ade Kurniawan (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
Mobile apps have come in dramatically in various fields and have changed people's lives. Developing effective mobile applications has become a significant problem for companies today to expand services or generate, and build a direct relationship with customers. Developing a mobile app requires challenging and testing various aspects. To deepen the knowledge of mobile apps requires a literature review. This paper provides basic knowledge about mobile applications and then continued evolution of mobile applications and mobile application challenges continued testing strategies and tools and frameworks for automation of android testing